2021
DOI: 10.54055/ejtr.v29i.2442
|View full text |Cite
|
Sign up to set email alerts
|

Job requirements in the hospitality industry: Technical or general skills? The dilemma for academic education

Abstract: This paper identifies the professional profiles of graduates for job positions in the accommodation sector, in particular, whether specific skills of the position or skills related to the tourism sector are preferred. A conjoint design is applied, which presents the more realistic context of asking respondents to evaluate potential “product” profiles. Managers of accommodation facilities expressed their preferences on four hypothetical profiles of candidates for five job positions: receptionist, administrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…Moreover, our research showed that employability is also significantly related to CIs. The cultivation of students’ employability is highly dependent on their education; however, there is a general disconnect between HTM education and the employability skills that the industries require [ 13 , 78 ]. Thus, developing students’ employability has become a common concern for communities, educational institutions, and industries [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our research showed that employability is also significantly related to CIs. The cultivation of students’ employability is highly dependent on their education; however, there is a general disconnect between HTM education and the employability skills that the industries require [ 13 , 78 ]. Thus, developing students’ employability has become a common concern for communities, educational institutions, and industries [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the tourism sector, specialized skills are more required than general ones in accommodation facilities for specific job positions (Varra et al, 2021). Soft skills in tourism, despite this remarkable impact on tourist satisfaction, are very often interpreted as a part of the natural order of things (Burns, 1997) which substantially increase customer satisfaction (Pretko, 2018).…”
Section: Soft Skillsmentioning
confidence: 99%
“…In recent years, interest in the field of human resources training has increased for several reasons: 1) a greater awareness of the need for skilled personnel able to satisfy tourists looking for increasingly intense experiences; 2) greater attention by universities to collaborate with firms; and 3) the higher education system has recognized the importance of the tourism sector for both research and education activities (Varra, et al, 2021). Numerous authors (Vara et al, 2021;Chiru et al, 2012;Connolly and McGing, 2006;Cristou, 1999;Jaykumar, Leena and Kandappan, 2014;Lupu, Tănase, and Nica 2014;Ruetzler et al, 2014;Zopiatis and Constanti, 2007) try to identify gaps between the needs of the tourism industry and the knowledge acquired in educational programs in their research.…”
Section: Hospitality Higher Educationmentioning
confidence: 99%
“…Today, broader management and information processing skills are required, as well as a whole range of soft skills (Westwood, 2004;Ritzer, 2004). Varra (2021) points out that two new necessary concepts for higher skills in tourism have finally been discovered in the literature. "Aesthetic skills" (Nickson et al, 2003;Warhurst et al, 2000), defined as the ability to respond to fashion or, especially in luxury hotel structures, to have good conversations about politics, music, sports, or the like.…”
Section: Hospitality Higher Educationmentioning
confidence: 99%